Analysis of lag time for December 2014 flood inccident in Kelantan River Basin, Malaysia - Nurul Fatyhah, Baharuddin (2016)
Kelantan River Basin is highly vulnerable to the risk of flood. Frequent flooding can cause a lot of cost property damages and losses of lives. December 2014 flood event was on an unprecedented scale due to extreme rain rate rainfall. The water level increase rapidly and the local people do not expected the situation become worst. These research focus of analysing lag time, (Δt) for flood event in Kelantan River Basin occurred during the end of December 2014 (from 20 until 31). The research area covered the area that effected during the flood event; Gua Musang, Kuala Krai, Tanah Merah, Pasir Mas and Kota Bharu. In this research, Auto-estimator method was used to derived hourly rain rate satellite-based rainfall data from satellite image of top of cloud temperature data taken from the public domain meanwhile the water level data obtained from Department of Irrigation & Drainage (DID).In addition, rain gauge hourly rainfall from DID also taken for comparison against satellite-based rainfall data. The estimated value and measured value shows a very good agreement (r = 0.905 to 0.99). The regression line fitted through origin has a slope of 0.811 to 1.134 the dataset. In this research there are three places to measure the water level starts from the upstream basin; Tangga Krai, Jambatan Guillemard and Tambatan DiRaja. From the analysis of the time series graphs of rainfall and river water levels show a lag time between the occurrence of first extreme rainfall in the upstream with water rising to the level of danger were 3,9 and 28 hours in Tangga Krai, Jambatan Guillemard and Tambatan DiRaja, respectively. Neglecting the lag time between rainfall and water level rise to dangerous level at Tangga Krai, it found that the lag time between the water level of danger at Tangga Krai and Jambatan Guillemard, also between Tangga Krai and Tambatan DiRaja were 6 and 17 hour. It comparable with DID records. On top of that, the satellite-based data from public domain able to be used for the flood forecasting in future will give benefit to relevant parties in future to ensure the systematic planning in flood management system.